Hans-Georg Gadamer en die Ou Testament - Roux, J. H. le (Verbum et ecclesia, 2002)
Hans-George Gadamer and the Old Testament Some aspects of Gadamer’s hermeneutics are discussed below: his view on method, the finiteness of being human, the value of prejudices and so forth. With Gadamer’s help we are also able to think anew about our South African Old Testament tradition. He has perspectives and concepts which can help us to reword the basic questions of Old Testament scholarship. Of course, Gadamer is but one possibility, but he was one of the most important thinkers of the twentieth century. Whoever struggles with him also gains insight into the hermeneutical perspectives of the twentieth century.